Modifying twisted nematic LCD screens to create dichromatic visual stimuli with LEDs. Issue 5 (30th March 2020) - Didion, Jeremiah E.; Smith, Karleigh; Layne, John E.
Abstract: The use of computers to create and display animations/videos in the study of visually guided behaviours has been instrumental in understanding sensory mechanisms underlying complex traits. Using computer displays, scientists are able to create a wide array of colours using three differently coloured lights (Red, Green, Blue [RGB]). While it is possible to generate scenes with RGB displays that mimic animals' colour perceptual experience, this can be problematic because it requires knowledge of the spectral absorbance of the animals' photoreceptor classes, which are often unknown and are difficult to obtain. Even then, stimuli are limited to the central part of the visible spectrum (e.g. ultraviolet (UV) stimuli are not possible). We present a cost‐effective way of modifying a twisted nematic LCD screen that utilizes coloured LEDs, that allows measuring animals' sensitivity to, and discrimination between, wavelengths of light. It has the benefit of not requiring a‐priori knowledge of animals' photoreceptor classes. An LCD screen can be modified by removing the screen's back polarizer (behind the liquid crystal layer) and backlighting the screen with LEDs of two different colours. One of the LED colours transmits through a polarizer with a transmission axis parallel to the screen's front polarizer, and other LED colour transmits through a polarizer orthogonal to the first. To test colour discrimination, one can create a dichromatic stimulus in which both LED colours are 'ON' and the current through one LED colour is decreased, while the other is constant, which generated a maximum intensity contrast of 1.84 log units in our setup. To test colour sensitivity, one can create a monochromatic stimulus in which only one LED colour is 'ON', which generates a contrast similar to the dichromatic stimulus. This technique overcomes many of the limitations of RGB‐based LCD screens in a cost‐effective way, and allows more accurate testing of the role of colour in visually guided behaviours. Besides the questions in vision research, this setup can answer, it can also be used as an outreach tool in classrooms where children can learn about light, colour, polarization and technology.